A Pediatric Resident Advocacy in Complex Care Curriculum - Ruchi Kaushik (Association of American Medical Colleges, 2023)
Introduction Children and youth with special health care needs (CYSHCN) are a special, vulnerable population. Children with medical complexity (CMC) represent a smaller, medically fragile sliver (6%) of the US child population. Several professional pediatric entities direct (or require) pediatric educators to instruct residents in advocacy for all children, explicitly including CYSHCN/CMC populations. While many existing curricula address pediatric advocacy education, a gap remains in curricula specifically designed to aid learners in advocacy of CYSHCN/CMC. Methods Using Kolb's experiential learning cycle as a framework, we designed and delivered a comprehensive outpatient complex care curriculum, including several didactic video lectures (total: 60:04 minutes, median: 6:25 minutes) and experiential site visits devoted to advocacy topics for CMC, as one portion of a 4-week elective complex care rotation. Residents completed pre- and posttests of knowledge and pre- and postsurveys to self-assess attitudes, comfort, and behavior; viewed didactic video lectures; and engaged in experiential site visits. Reflective statements captured attitudes regarding advocacy for CMC. Results Between July 2016 and June 2020, 47 trainees completed the rotation; data were available for 30 trainees. Residents demonstrated a statistically significant improvement in knowledge (p < .001), as well as improved attitudes, diversity sensitivity, and comfort in advocating for CMC postrotation. Qualitative comments showed overwhelmingly positive learner reaction. Discussion This curriculum, which can be offered as a stand-alone resource or a supplement to a comprehensive complex care curriculum, incorporates didactic and experiential teaching methods and addresses a significant competency in advocacy education.